x^3-7x-6=0
x^3+x^2-(x^2+7x+6)=0
x^2(x+1)-(x+1)(x+6)=0
(x+1)(x^2-x-6)=0
(x+1)(x-3)(x+2)=0
x=-1,或 x=3,或 x=-2
2x^3-3x^2-9x+10=0
2x(x^2-2x+1)+x^2-11x+10=0
2x(x-1)^2+(x-1)(x-10)=0
(x-1)(2x^2-x-10)=0
(x-1)(2x-5)(x+2)=0
x=1 或 x=5/2 ,或 x=-2
x^4-5x^3+5x^2+5x-6=0
x^4-5x^3+4x^2+x^2+5x-6=0
x^2(x-4)(x-1)+(x-1)(x+6)=0
(x-1)(x^3-4x^2+x+6)=0
(x-1)(x^3-4x^2+3x-2x+6)=0
(x-1)(x(x-3)(x-1)-2(x-3))=0
(x-1)(x-3)(x^2-x-2)=0
(x-1)(x-3)(x-2)(x+1)=0
x=1 、3、2、-1
3x^3-10x^2+9x-2=0
3x(x^2-3x+2)-(x^2-3x+2)=0
(3x-1)(x^2-3x+2)=0
(3x-1)(x-2)(x-1)=0
x=1/3 、 2、 1